MODIFICATION OF HAND HOLE VALVE IN 10 KG CAPACITY MINI GASIFIER MACHINE - Koeshardono, Fachri (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2020)
Coal is one of the fossil fuels generally is that sedimentary rocks can ignite, formed from organic deposits. Along with the depletion of reserves of fossil energy sources, there is a coal energy conversion technology that is the gasification process. Gasification is a thermos-chemical conversion process from solid material to gas fuel that can be used for various needs. Tools for the gasification process are called gasifiers, one type of which is a fixed bed gasifier. A fixed bed gasifier is a gasification system using a number of solid fuels (coal / biomass) through which air and gas can pass either up or down. This type is the simplest type used on a small scale, this gasifier tool is usually small and often called a mini gasifier. Generally, there are major gasifier mini parts namely; hopper, reactor, water storage, steam drum, cyclone separator, spliter, and blower. Mini gasifier has a problem in the hand hole valve which is in the reactor section where the hand hole valve is difficult to open and close or impractical because it uses as many as eight bolts so that the alignment of the bolt so that the bias is closed tightly, it is necessary to improvise a new design on the hand hole valve deal with the problem. Two alternative designs were made to determine the right solution, design A in the form of an acetyline gas valve and design B in the form of a modification of the valve that was pre-installed on the reactor. Hand hole B valve design was chosen as a solution to handle this problem.